Assessment of the Level of Awareness and Knowledge of Covid-19 among rural population in Khulna, Bangladesh (Mediscope, 2024)
Objective: The objective of the study was to find out level of Awareness and knowledge about covid-19 among rural population in Bangladesh.Methods: A cross-sectional descriptive type of study was carried out in Bathiaghata Upazilla, Khulna from 25.11.21 to 25.12.2021. Adult persons, 455 (male 181 and female 274) with mean age ± SD was 24 ±1.5 years, selected purposively from the households in the adjacent villages were included in the study as respondents.Results: Among the respondents, 97.4% heard about covid-19. Of them, 292 (71.6%) had knowledge that the disease is transmitted by cough, sneezing, direct contact and the proportion of the respondents who knew about symptoms like high fever, headache, cough, loss of taste and loss of smell were 50.1%, 16.7%,16% and 7.4%, respectively. Most of the respondents received health care services from MBBS doctors (87.3%). The majority of the respondent (76.5%) identified who heard about prevention of covid-19 by wearing mask, as a good preventive practice against covid-19 infection, followed by frequent hand washing (18.4%) which is eventually important for the prevention of covid-19.Conclusion: It was a unique study that describing adult heath related knowledge on covid-19 among adult population in a rural area. The study results suggest a further need to strengthen health education about covid-19 among rural population in Bangladesh.Mediscope 2024;11(2): 62-67